Methodology of Testing Foil Bearings in the Start-Stop Cycle in the Presence of a Working Medium - Stabilization of Temperature in the Test Chamber (Agricultural Engineering, 2020)
The article presents the methodology of testing sliding bearings with a flexible shell, focusing on the issue of temperature increase during experiments for a specific time interval of the START-STOP test cycle. Selected material pairs, used in previous studies, were used in the experiment. The stand used for tests in the start-stop cycle was developed under the project POIG.01.03.01-00-027 / 08-00 at the Faculty of Technical Sciences UWM in Olsztyn.